The Readiness of Print Media Human Resources in the Digital Transformation Process (A Case Study of Gorontalo Post) - Mohamad Caisar Ntoma; Arifin Tahir; Sudarsono (ABM: International Journal of Administration, Business and Management, 2025)
Changes in people's information consumption behavior in today's digital era require print media outlets like Gorontalo Post to begin implementing adaptive work strategies. To support the implementation of these work adaptation strategies, several key elements are needed to make the necessary changes. One of these essential elements is the readiness of human resources (HR) to adapt to technological developments and the work Environment. This research uses a case study Analys and a qualitative approach to analyze Gorontalo Post's HR readiness to implement the digital transformation process, focusing on digital competency, attitudes toward change, and managerial support. Following participant observation, in-depth interviews, and internal document analysis, data were collected and analyzed using a SWOT analysis. The results indicate that Gorontalo Post's HR has the ability to adapt, but they still face obstacles such as limited digital competency, resistance to change, and a weak internal training strategy.